Graduates' employment according to vocational education institutions monitoring - L. M. Serova; K. A. Mazaeva (Moscow Polytechnic University, 2022)
The article presents the monitoring results of vocational education institutions graduates' employment in 2012 in terms of territory, aggregated occupation groups, types of economic activity, business levels and profession groups.